Total antioxidant activity, total phenolic content and radical scavenging activity both flesh and peel of red pitaya, white pitaya and papaya - Mohd Adzim Khalili, Rohin; Abd Manaf, Ali; Che Abdullah, Abu Bakar (2012)
Red playa as knows to ham a mutate' el nutneonef Watts ,ncleang cholesiefaleoeenng elects. polo-Oa against dogmas and came. rhe olaectnrs d Ms study was to evaluate mill Irtheein cartactly IOU phereeC COnin and reeell eCadncong sadly d both Zeta and peal Of lea foss" *ate playa Ina papeya al The gehh" dchleeomedume (00.41 eehd Kfle (EA) wed armed extract, Bated on th. results *paned the tested but extracts thoeed sOona anhoaadlint aChaty a claerentar capEny to elstal tad Detenotalben by FTC and IBA method wench ts ad/gated by them taw absabanct Pea grew conceferebon the ielanely hats sem/ was resented In me news of fed playa lash katheed red playa Peel- eerie Playa Rest` stele playa Peet papaya Rein and papaya peel toPest") Me slant/ of wolfed grgeghiCk eneoedeta. aloCcepheeol and BHT Red playa One Showed 10* WKS tehterg Elanty as CCenNage310 BHA b right II's^ BHT and a- tggeghged kkggn9 that red Piths hash comanei Pugh amount of motel acavengmg comp:tads Red pats fifth also ahaned the heat reducthe Wats as compared watt` ante playa fest, papaya teals red peso peel elute playa peel end papaya peel The hat Rash extracts eases, see bow lean aiocopherol BHA and MIT shindereS teal these 011ererces earsstaIrstKagy Very stgnfichee lo<0 04) Sworroze. raekal scateatin actrety al those samples Wowed the 046er Bat/0BM salocoplsotoland playa fitsh, Mee playa faShn'aflaP hewed playa peel, papaya peat-node playa peel Red playa flesh thane be reica scasenseng arises as cornmeal* BHA but greater than BHT and a 10<cl:hetet slannsg that red playa lash screamed NO emoted of faecal sca,torand comecca:Is